West Gondwanaland during and after the Pan-African and Brasiliano orogenies:downslope vectors and detrital-zircon U–Pb and T DM ages and εHf/Nd pinpoint the provenances of the Ediacaran–Paleozoic molasse - Veevers, J. J. (Earth-Science Reviews, 2017)
The Pan-African and Brasiliano orogenies endowed West Gondwanaland with U–Pb 700–500 Ma zircons, which, together with 1200–1000 Ma zircons from Rodinian collisions, are scattered in the Ediacaran–Paleozoic syn- and post-tectonic molassic outflow from the orogens. A more complete (T DM , εHf) isotopic signature in places narrows the search for provenance but exclusive use of the signature is of limited value given the ubiquity of primary and secondary 700–500 Ma and 1200–1000 Ma zircons. To overcome this shortcoming, I link the detrital-zircon signature with paleogeographical indicators of downslope preserved in minor sedimentary structures generated by gravity currents: the cross-dip azimuth in fluvial sediments, flute marks and other vectorial markings in turbidites. The prominent East African-Antarctic Orogen (EA-AO) trends through Africa-Arabia southward through East Africa/Madagascar to Dronning Maud Land in Antarctica. Squire et al. (Squire et al., 2006. Did the Transgondwanan Supermountain trigger the explosive radiation of animals on Earth? Earth and Planetary Science Letters 250, 116–133) postulated > 8000-km-long and > 1000-km-wide Transgondwanan Supermountains (TGSM) atop the EA-AO that resulted in extreme erosion and sedimentation rates; super-fans of quartz sand spread across continental North Africa-Arabia and oceanic crust offshore East Gondwanaland, as seawater 87 Sr/ 86 Sr rose to a maximum. Downslope indicators and the isotopic signature confirm the suggested deposition of the enormous North African-Arabian Super-fan from the Oubanguides Orogen-TGSM (Burke et al., 2003. Africa's petroleum systems: four tectonic 'Aces' in the past 600 million years. Geological Society of London Special Publications 207, 21–60), and the Cape Group from the TGSM. Other major provenance → sink relations are the Oubanguides Orogen → Congo Basin and the Damara Orogen and Dom Feliciano Orogens → Nama Basin. Minor and proximal provenance → sink relations are the Tuareg Shield and the Dahomeyides-Nigerian Shield → ...